Análise dos impactos do lançamento de esgotos em um trecho da rede de drenagem com exultório no bairro 13 de julho em Aracaju - Soares, Joyce Helly da Anunciação (2022)
The accelerated growth and urban development in the cities, associated with population growth, and lack of proper planning, are related to large loads of waste produced and environmental impacts, when these are released irregularly into the environment. When combined with deficient urban sanitation systems, it causes negative social, environmental, and/or economic externalities. The inadequate disposal of sanitary wastewater is one of the main causes of water resource pollution in Brazil. Therefore, the sewage flowing into the stormwater system also contributes significantly to this pollution. Therefore, the study aims to analyze at the process of contamination of the drainage channel with exultory located in the Treze de julho District, to identify the relationship with possible irregular connections of sanitary sewage. By using the hypotheticaldeductive method and a quantitative and explanatory research, set out to test the hypothesis. The research highlights consisted of field research, with direct observation to verify critical points of the drainage channel and the release point in the Sergipe River, and experimental research, with sample collection from the drainage channel. In a historical contextualization it was verified how the initial deficient functioning of the sanitation services influenced the occurrence of clandestine connections and the improper disposal of effluents. A contemporary analysis showed that the values of TDS and fecal coliforms indicate contamination of the drainage network by the presence of sanitary sewage. However, BOD presented concentrations below the characteristics of sewage discharged in natura. Regarding the significant difference for the location of the collection point and regarding seasonality, it is concluded that the main factor of influence in the composition of the water of the drainage network under study is the carriage of pollutants from surface runoff in periods of higher precipitation. Finally, the critical flood points in the Treze de Julho neighborhood presented impacts and risks regarding urban mobility, health and economic order.